2012
DOI: 10.1021/ol301007h
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphate Tether-Mediated, One-Pot, Sequential Ring-Closing Metathesis/Cross-Metathesis/Chemoselective Hydrogenation Protocol

Abstract: A versatile three-step, one-pot, sequential reaction protocol involving RCM, CM, and chemoselective hydrogenation is reported. This phosphate tether-mediated process occurs without intermediate isolation, is chemoselective and is governed by stereoelectronic properties innate to phosphate tethers, which ultimately act to preserve the integrity of the bisallylic, bicyclic phosphate for subsequent nucleophilic additions. Overall, this process can be used to efficiently generate advanced polyol synthons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…[4] Over the past decade, we have investigated the use of phosphate tethers to access complex polyol fragments via the desymmetrization of 1,3- anti -diol subunits using ring-closing metathesis (RCM) and one-pot, sequential RCM/CM/hydrogenation protocols. [5] In this regard, reported studies have focused solely on the use of simple allyl alcohol coupling partners to synthesize bicyclo[4.3.1]-phosphates en route to the syntheses of bioactive natural products. [6] Despite obvious attributes, a thorough understanding of the behavior of phosphate tethers across a wide range of substrates represents a notable deficiency that impedes general applicability of the method—as well as extensive use—in the synthesis of biologically active small molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Over the past decade, we have investigated the use of phosphate tethers to access complex polyol fragments via the desymmetrization of 1,3- anti -diol subunits using ring-closing metathesis (RCM) and one-pot, sequential RCM/CM/hydrogenation protocols. [5] In this regard, reported studies have focused solely on the use of simple allyl alcohol coupling partners to synthesize bicyclo[4.3.1]-phosphates en route to the syntheses of bioactive natural products. [6] Despite obvious attributes, a thorough understanding of the behavior of phosphate tethers across a wide range of substrates represents a notable deficiency that impedes general applicability of the method—as well as extensive use—in the synthesis of biologically active small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts towards synthesis of 1,3-anti-diol containing natural products utilizing phosphate tether-mediated selective reactions [5,6] led to application for dictyostatin, a marine macrolide with promising antitumor and anticancer activities. [8] Retrosynthetic analysis of fragments 2 or 3 (Scheme 1) revealed that 1 could, in theory, be constructed via a phosphate tether-mediated tripodal coupling of POCl 3 , C 2 -symmetric diene diol ( S,S )- 7 and olefin partner 6 , followed by RCM to yield the bicyclo[5.3.1]- and [7.3.1]-phosphates 4 and 5 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Following optimized conditions for one-pot, sequential RCM/CM/[“H 2 ”], 15 triene ( S,S )- 8 was subjected to an RCM reaction using the second-generation Hoveyda-Grubbs catalyst 16 ( HG-II ) (2 mol %) in refluxing CH 2 Cl 2 (Scheme 2). After RCM completion (30 min), the solvent was changed 17 to 1,2-dichloroethane (DCE) and the n -pentyl-substituted CM partner 9 was introduced to the same pot, followed by a second addition of HG-II (4 mol %).…”
mentioning
confidence: 99%
“…Efforts to macrolactone 1a began by employing a phosphate tether-mediated one-pot, sequential RCM/CM/chemoselective hydrogenation[“H 2 ”] protocol [28] to couple phosphate triene ( R,R )- 4 and cross-metathesis (CM) partner 5 , providing bicyclic afforded phosphate triester 6 in 40% overall yield over the course of three reactions, representing an average yield of 74% for each reaction (74% av/rxn, Scheme 2). By exploiting the orthogonal leaving and protecting group ability of bicyclic phosphate 6 , we next applied a one-pot Pd-catalyzed, reductive allylic transposition and phosphate tether removal protocol [29g] (Scheme 2).…”
mentioning
confidence: 99%